2014
DOI: 10.1111/jasp.12241
|View full text |Cite
|
Sign up to set email alerts
|

Enjoyment of sexualization: is it different for men?

Abstract: We elucidated the Enjoyment of Sexualization (ES) construct in a sample of 206 female and 118 male undergraduate students. Our male ES Scale had high reliability, and confirmatory factor analyses indicated that a univariate structure was appropriate for both men and women. ES added to the prediction of self‐esteem and number of sexual partners (but not body shame) after controlling for self‐objectification; gender did not moderate these relationships. The relationship between ES and number of sexual partners w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
6
17
0
5
Order By: Relevance
“…The sexual appeal of men has become a central feature in contemporary traditional media (e.g., Leit et al, 2002;Ward et al, 2015) and social media, with men increasingly focusing on their own sexual appeal in the selfies they post online (Döring et al, 2016). Such findings confirm earlier reports of boys' being motivated to alter their bodies in order to approach the ideal (e.g., McCabe & Ricciardelli, 2001) and men's enjoying sexualization just as much as women do (Visser, Sultani, Choma, &, 2014;. Additionally, this study's findings corroborate earlier body image research indicating that there are no differences between women and men in how social media relate to body image outcomes, such as enjoyment of being perceived as a sex object and body surveillance (e.g., Manago et al, 2014;Vandenbosch & Eggermont, 2012).…”
Section: Gender Similaritiessupporting
confidence: 76%
“…The sexual appeal of men has become a central feature in contemporary traditional media (e.g., Leit et al, 2002;Ward et al, 2015) and social media, with men increasingly focusing on their own sexual appeal in the selfies they post online (Döring et al, 2016). Such findings confirm earlier reports of boys' being motivated to alter their bodies in order to approach the ideal (e.g., McCabe & Ricciardelli, 2001) and men's enjoying sexualization just as much as women do (Visser, Sultani, Choma, &, 2014;. Additionally, this study's findings corroborate earlier body image research indicating that there are no differences between women and men in how social media relate to body image outcomes, such as enjoyment of being perceived as a sex object and body surveillance (e.g., Manago et al, 2014;Vandenbosch & Eggermont, 2012).…”
Section: Gender Similaritiessupporting
confidence: 76%
“…So, sexual objectification experience is one of the important factors to predict female students' selfie-posting behavior. Mediation analysis showed that Enjoyment of Sexualization plays a partial mediating role between sexual objectification experience and selfie-posting behavior, which verified hypothesis H2 and is consistent with the previous research (Barnett, Maciel, & Gerner, 2018;Visser, Sultani, Choma et al, 2014). Impression management theory points out that individuals tend to adopt strategies to control others' impressions on themselves to achieve a good impression (Liu, 2006), such as presenting or publishing information that is beneficial to their body image.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, it could be fruitful, as suggested by Calogero and colleagues (2009), to carry out qualitative studies in which participants face in-depth interviews or focus-group situations with real experiences in order to provide insight into the lesser-known aspects involved in women’s reactions to different kinds of comments/compliments. In the future, it may also be advantageous to extend these studies to include men so as to explore not only how they feel when receiving objectification messages (Visser, Sultani, Choma & Pozzebon, 2014), but also how they perceive objectification when they make comments on women’s appearance and sexual body. There also needs to be more in-depth research done into other forms of interpersonal objectification (e.g., objectifying gazes, Gervais, Vescio, & Allen, 2011; cat-call remarks, Chaudoir & Quinn, 2010), both within and beyond romantic relationships, a virtually uncharted area of research to date.…”
Section: Discussionmentioning
confidence: 99%